Mass spectrometry of analytical derivatives. 2. “Ortho” and “Para” effects in electron ionization mass spectra of derivatives of hydroxy, mercapto and amino benzoic acids() - Todua, Nino G. (Mass Spektrom, 2016)
Derivatives requiring either anhydrous or aqueous reaction conditions were prepared for robust and reliable gas chromatography/mass spectrometry (GC/MS) characterization of hydroxyl, mercapto, and amino benzoic acids Methylation and trialkylsilytation are employed for blocking the acidic function. Alkyl, trimethylsilyl, acetyl, perfluoroacyl and alkoxycarbonyl derivatization groups are introduced to hydroxyl, mercapto and amino functions. The electron ionization induced fragmentation characteristics of corresponding derivatives are explained by comparing the MS(1) spectra of unlabeled compounds to their (2)H and (13)C labeled analogs, and analysis of collision-induced dissociation data from MS(2) spectra. Competing fragmentation alternatives are identified and specific decomposition processes are detailed that characterize (a) ortho isomers due to interaction or vicinal functional substituents and (b) para isomers prone to forming para quinoid type structures. Skeletal and hydrogen rearrangements typical for methyl benzoates and the blocking groups are considered when discussing diagnostically important ions. Characteristic ions produced as a result of rearrangements in ortho isomers are classified, and skeletal rearrangements required to produce para quinoid type ions specific for para isomers are noted. Key ions for structure elucidation and differentiation of isomers for derivatives of substituted benzoic acids by GC/MS are suggested.